2000
DOI: 10.1115/1.1308570
|View full text |Cite
|
Sign up to set email alerts
|

Impeller–Diffuser Interaction in a Centrifugal Compressor

Abstract: A study has been conducted, using an unsteady three-dimensional Reynolds-averaged Navier-Stokes simulation, to define the effect of impeller-diffuser interaction on the performance of a centrifugal compressor stage. The principal finding from the study was that the most influential aspect of this unsteady interaction was the effect on impeller tip leakage flow. In particular, the unsteadiness due to the upstream potential effect of the diffuser vanes led to larger viscous losses associated with the impeller ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 12 publications
4
25
0
Order By: Relevance
“…14), which results in high values of absolute angle. Figure 15 shows the difference between the absolute flow angle calculated near surge and the absolute flow angle calculated at peak According to Shum et al [5] who stated that the diffuser performance is mainly influenced by the incidence of the time-averaged flow, it is thought from the results given in Figs 14 and 15 that the strong instabilities inception could be initiated near the hub of the vaned diffuser entry zone. Moreover, it has been shown [14] that, at peak efficiency, the wake material migrated in the vaned diffuser passage towards the hub, leading to an accumulation of low momentum fluid near the hub.…”
Section: Flow Structure In the Impellermentioning
confidence: 95%
“…14), which results in high values of absolute angle. Figure 15 shows the difference between the absolute flow angle calculated near surge and the absolute flow angle calculated at peak According to Shum et al [5] who stated that the diffuser performance is mainly influenced by the incidence of the time-averaged flow, it is thought from the results given in Figs 14 and 15 that the strong instabilities inception could be initiated near the hub of the vaned diffuser entry zone. Moreover, it has been shown [14] that, at peak efficiency, the wake material migrated in the vaned diffuser passage towards the hub, leading to an accumulation of low momentum fluid near the hub.…”
Section: Flow Structure In the Impellermentioning
confidence: 95%
“…Shum et al [10] found that the alignment of the diffuser vanes with a spatially averaged and time-averaged impeller exit flow was the main parameter affecting the diffuser performance. Shum et al also conclude that there is an optimum radial gap between the impeller exit and diffuser leading edge, because at some decreasing radius, increasing losses overtake the benefits of a smaller blockage achieved with a smaller radial gap.…”
Section: Nomenclaturementioning
confidence: 99%
“…This aspect has been documented by several researchers (see, among others [3,4]). Owing to this complexity, some authors have underlined the weak points of a simple approach that attempts to describe the flow entering the diffuser without the direct effect of impeller interaction [5][6][7]. On the other hand, with the help of both experimental and numerical simulations, other researchers have indicated that the circumferential non-uniformities are less important than those occurring from hub to shroud in the neighborhood of the best efficiency working point [3,8].…”
Section: Introductionmentioning
confidence: 98%